A review of sensing, uptake, and environmental factors influencing nitrate accumulation in crops. (21st April 2021) - Htwe, Nang Myint Phyu Sin; Ruangrak, Eaknarin
Abstract: Available nitrogen (N) in the soil is an essential mineral element for plant growth and development. Nitrate (NO3 – ) is one component among the N sources for higher plants that can be taken up by the roots and translocated to the shoots for reduction or for storage in vacuoles. The edible parts of the plants, especially in leafy vegetables, may accumulate large amounts of this ion, which may contribute to several adverse health effects in consumers. In this review, we focus on how the nitrate behaves as a local nutrient and systemic signal for molecular, metabolism, physiology, and other plant development. We also discuss how nitrate uptake by the plant system relies on the N status of the plant itself, and on the developmental stages of the root. In addition, we also detail review how the various environmental factors, such as light, temperature, nutritional conditions and water status are involved as key nitrogen sources contributing to the nitrate accumulation in the plant. A better understanding of environmental factors that affect N- sources of the nitrate content could support improving quality of crop productivity and enhance availability of healthy food to consumers.